2017
DOI: 10.1007/s00213-017-4526-8
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral evidence for the abuse potential of the novel synthetic cathinone alpha-pyrrolidinopentiothiophenone (PVT) in rodents

Abstract: Our results indicate that alpha-PVT has rewarding and reinforcing effects and shares the interoceptive effects of cocaine and methamphetamine. To the best of our knowledge, the present study is the first to show that alpha-PVT has reinforcing properties when delivered on its own, which suggests possible abuse liability in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 28 publications
2
39
0
Order By: Relevance
“…4-MePPP did not fully substitute for cocaine in rats (Gatch et al, 2015a), nor did mephedrone (4-methylmethcathinone) fully substitute in rhesus monkeys (Smith et al, 2016), despite fully substituting for cocaine in rats (Gatch et al, 2013). It should be noted that α-PVT has been reported to produce full substitution in both cocaine- and methamphetamine-trained rats (Cheong et al, 2017), although that study used a lower training dose of cocaine (5.6 mg/kg). There is still a possibility that mephedrone does not have robust cocaine-like discriminative stimulus effects as rats trained to discriminate mephedrone from saline did not fully generalize to cocaine (Varner et al 2013).…”
Section: Discussionmentioning
confidence: 95%
“…4-MePPP did not fully substitute for cocaine in rats (Gatch et al, 2015a), nor did mephedrone (4-methylmethcathinone) fully substitute in rhesus monkeys (Smith et al, 2016), despite fully substituting for cocaine in rats (Gatch et al, 2013). It should be noted that α-PVT has been reported to produce full substitution in both cocaine- and methamphetamine-trained rats (Cheong et al, 2017), although that study used a lower training dose of cocaine (5.6 mg/kg). There is still a possibility that mephedrone does not have robust cocaine-like discriminative stimulus effects as rats trained to discriminate mephedrone from saline did not fully generalize to cocaine (Varner et al 2013).…”
Section: Discussionmentioning
confidence: 95%
“…16 Recent research on the pyrovalerone analogue α-pyrrolidinopentiothiophenone (α-PVT) suggests it has reinforcing and rewarding effects similar to those of both methylamphetamine and cocaine. 17 It has been suggested that the reinforcing properties of cathinone stimulants are positively correlated with their selectivity for the dopamine (DAT) relative to SERT. 15,[18][19][20] What is already known about this subject • NPSfinder ® has identified some 41 cathinone molecules not known to either the UNODC or EMCDDA.…”
Section: Clinical Neuropharmacological Issuesmentioning
confidence: 99%
“…MDPV and α‐PVP are both considered to be cocaine‐like, whilst being more effective reinforcers . Recent research on the pyrovalerone analogue α‐pyrrolidinopentiothiophenone (α‐PVT) suggests it has reinforcing and rewarding effects similar to those of both methylamphetamine and cocaine …”
Section: Introductionmentioning
confidence: 99%
“…Significance place conditioning was additionally observed for the phenyl/thiophene substitute of α -PVP, α- pyrrolidinopentiothiophenone ( α -PVT). 67…”
Section: Behavioral Effects Of Synthetic Cathinones Determined From Cmentioning
confidence: 99%